2011
DOI: 10.1590/s0100-29452011005000048
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade de abelhas visitantes das flores de Citrus em pomares de laranjeira e tangerineira

Abstract: RESUMO-A presença de abelhas em culturas de valor comercial, no período de florescimento, é importante não apenas para garantir a polinização cruzada, quando indispensável, mas também para incrementar a produção de frutos e sementes. Nessa perspectiva, o presente trabalho teve a finalidade de identificar as abelhas visitantes das flores em pomar de laranjeira (Citrus sinensis) e tangerineira (Citrus reticulata) em Salinas -MG. O trabalho foi conduzido na fazenda experimental Santa Isabel, da Escola Agrotécnica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(10 reference statements)
2
3
0
2
Order By: Relevance
“…Of this total, the Apidae Family stood out with 99.00%, while the other Families (Andrenidae, Halictidae and Megachilidae) with percentages lower than 1%. In the present study, we observed a high association between species of the Apidae family and the species under study, with percentages similar to those observed in the present study (MALERBO-SOUZA NASCIMENTO et al, 2011).…”
Section: Couto (2002)supporting
confidence: 91%
See 3 more Smart Citations
“…Of this total, the Apidae Family stood out with 99.00%, while the other Families (Andrenidae, Halictidae and Megachilidae) with percentages lower than 1%. In the present study, we observed a high association between species of the Apidae family and the species under study, with percentages similar to those observed in the present study (MALERBO-SOUZA NASCIMENTO et al, 2011).…”
Section: Couto (2002)supporting
confidence: 91%
“…Nascimento et al (2011) studying three varieties of Citrus sp in Salinas, MG, found high similarity between two orchards in full bloom with seasons similar to those of the present work. The authors stated that the causes of similarity are due to the large population of A. mellifera.…”
Section: Couto (2002)supporting
confidence: 86%
See 2 more Smart Citations
“…It is considered a mid-season fruit, which is harvested primarily from May to June and due to seasonality, there is a need to extend its offer to other periods of the year (Nascimento et al, 2010). About 960 tons of tangerines are harvested annually in the country (IBGE, 2012).…”
Section: Introductionmentioning
confidence: 99%